THE EFFECT OF BRAND IMAGE AND STORE ATMOSPHERE ON CUSTOMER PURCHASE DECISION AT CONFLUX COFFEE TOMOHON - Teneh, reynald; Pandowo, Merinda H.C.; Wangke, Shinta J.C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This study aims to examine the effect of brand image and store atmosphere on customer purchase decisions at Conflux Coffee Tomohon. The research employs a quantitative approach, using a survey method to collect data from a sample of Conflux Coffee customers. The variables studied include brand image, store atmosphere, and purchase decision. Data analysis is conducted using multiple regression analysis to determine the influence of brand image and store atmosphere on the customers' purchasing behavior. The results indicate that both brand image and store atmosphere significantly influence customer purchase decisions. A positive brand image enhances customer trust and loyalty, making them more likely to choose Conflux Coffee over competitors. Meanwhile, a comfortable and appealing store atmosphere creates a pleasant experience that encourages customers to spend more time and make repeat purchases. Among the two variables, brand image has a stronger influence on purchase decisions, highlighting the importance of consistent brand management and marketing strategies. This study concludes that Conflux Coffee Tomohon should focus on maintaining a positive brand image and creating a welcoming store atmosphere to improve customer satisfaction and purchasing decisions. The findings can serve as a reference for other coffee shops aiming to strengthen their competitive advantage through brand image and store atmosphere optimization.   Keyword: Brand Image, Store Atmosphere, Purchase Decision